Application of GBT theorem for Gravitational deflection of light by Compact Objects - Beissen, N.A.; Utepova, D.; Muratkhan, A.; Orazymbet, A.; Khassanov, M.; Toktarbay, S. (Recent Contributions to Physics, 2023)
One of the most renowned classical experiments that verifies the curved nature of space-time geometry is the bending of light. This phenomenon is extensively discussed in most textbooks on general relativity, with a clear and comprehensive explanation provided. In this study, we employ the material medium approach to determine the refractive index associated with the gravitational field of a compact object with a quadrupole moment. Our research presents a method for calculating the gravitational deflection angle for compact objects by utilizing the refractive index and the GBT theorem for an isotropic metric. This method is particularly important because it allows for the calculation of the deflection angle for both light and relativistic particles. The material medium approach enables us to consider the compact object's gravitational field as a medium with a refractive index. By applying this approach, we establish a relationship between the refractive index and the quadrupole moment of the compact object. We then utilize this relationship to calculate the deflection angle of light and relativistic particles.